Keamanan Maritim dan Implikasi Kebijakannya Bagi Indonesia - Keliat, Makmur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2009)
Through the last decade the concept of Maritime Security has been discused in many global and regional forum such as UN and ASEAN. Common agreement on the concept of Marine Security, however, have not been reached. Among the long debate is between traditional and non-traditional approach. Recent development shows a more accommodation toward the non-traditional approach. For Indonesia, this development has increased the need to a more integrated maritime security policy. This paper argues that in order to create an integrated maritime security policy, Indonesia should differs its maritime into specific zones with specific role while at the same time promoting network among actors and stakeholders.